Peranan Jurnalis Islam di Era Globalisasi : Analisis terhadap Kiprah Wartawan pada Tabloid Gema Baiturrahman Kota Banda Aceh - Asmaunizar Asmaunizar; Abdullah (Sadida Islamic Communications and Media Studies, 2024)
This research is entitled the role of Islamic journalists in the Era of Globalization (Analysis of the Gait of Journalists at Tabloid Gema Baiturrahman Banda Aceh City). The purpose of this research is to find out how the gait of Muslim journalists at Tabloid Gema Baiturrahman in positioning themselves as da'I in the world of the press. In this study the authors used descriptive qualitative method. The results of the study state that the work of Muslim journalists on the Baiturrahman Echo Tabloid has fulfilled the role of Muaddib (Educator), Musaddid (straightening Information), Mujaddin (Renewal), Muwahhid (spokesman for the people) and Mujahid (Islamic fighters). In addition, Tabloid Gema Baiturrahman has also been based online so that it can be accessed by all internet users.